2003
DOI: 10.2144/03354st04
|View full text |Cite
|
Sign up to set email alerts
|

Selection of candidate housekeeping controls in tomato plants using EST data

Abstract: Because the expression levels of housekeeping genes are relatively constant in most tissues, they are often useful controls when quantifying gene expression. We present an analytical method for identifying candidate housekeeping controls using expressed sequence tags (ESTs) from The Institute for Genomic Research Tomato Gene Index. We found relative expression levels for a collection of 127 transcripts and calculated the percentage of cDNA libraries that had expression levels (for a given transcript) within 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 21 publications
2
66
0
Order By: Relevance
“…The cDNA abundance of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a cytosol and plastid glycolytic enzyme, was similarly high in both libraries, four ESTs in each ( Table 3), suggesting that it is perhaps one of the housekeeping genes, a view also supported by a recent analysis of tomato ESTs (Coker and Davies 2003). However, since several nuclear-encoded isoforms of GAPDH exist in plant cells, we conducted a close bioinformatic analysis of GAPDH ESTs via manual BLAST search against the Arabidopsis protein database.…”
Section: Clustering Analysis To Generate Unique Transcriptsmentioning
confidence: 69%
“…The cDNA abundance of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a cytosol and plastid glycolytic enzyme, was similarly high in both libraries, four ESTs in each ( Table 3), suggesting that it is perhaps one of the housekeeping genes, a view also supported by a recent analysis of tomato ESTs (Coker and Davies 2003). However, since several nuclear-encoded isoforms of GAPDH exist in plant cells, we conducted a close bioinformatic analysis of GAPDH ESTs via manual BLAST search against the Arabidopsis protein database.…”
Section: Clustering Analysis To Generate Unique Transcriptsmentioning
confidence: 69%
“…Sequence-based approaches such as EST, SAGE were also used in housekeeping gene studies (Velculescu et al 1999;Coker and Davies 2003;Zhu et al 2008), however most of them are relatively low throughput ). Until recently high-throughput next-generation sequencing based RNA-seq provided an appealing alternative to mining housekeeping genes in a high-throughput and relatively unbiased fashion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhu et al (2008) analyzed human EST libraries and found 3,140 to 6,909 annotated genes were universally expressed. Coker and Davies (2003) used EST data to select candidate housekeeping controls in tomato. However, EST based method is relatively low throughput, expensive and generally not quantitative ).…”
mentioning
confidence: 99%
“…The tubulin cDNA was used as reference. Tubulin has been accepted widely as housekeeping gene in growing plants (Coker and Davies 2003). PCR was carried out in a 0.02 cm 3 reaction containing a 1 Ă— SYBR Green PCR master mix (Tiangen, Beijing, China), 500 nM forward and reverse primers, and 0.002 cm 3 of cDNA template.…”
Section: Methodsmentioning
confidence: 99%